Determinants Of Earning Persistence In Consumer Cyclicals Sector In Indonesia - Hendro Lukman; Phebe Callista (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Companies need income persistence in maintaining performance in the capital market. Income persistence will be a consideration for investors in making investment decisions. This study analyzes the factors of total accruals, real earnings management, cash flow volatility, and leverage that can affect income persistence in consumer cyclicals companies listed on the Indonesia Stock Exchange in 2017-2020. Sampling method with purposive sampling method. There were 42 samples that met the criteria. The analysis used multiple regression analysis which was processed using SPSS 22. The research showed that total accruals, cash flow volatility, and leverage had no effect on earnings persistence, but real earnings management showed an effect on income persistence. However, real earnings management showed effect on earnings persistence. The implication of this research is that every company must pay attention to these four factors in the current year so that it shows good and resilient corporate finance which can provide a positive signal for investors so that it increases the company's share price in the capital market.